ANALYSIS OF AFLATOXIN B1, B2, G1, G2 LEVELS IN FRIED ONIONS PRODUCED IN PALU USING HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) METHOD - Ayu Warmadewi, Putu; Utama, Qabul Dinanta (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2024)
Aflatoxin, produced by Aspergillus flavus and Aspergillus paraciticus, commonly contaminates agricultural and processed products. This study aims to analyze aflatoxin levels in fried onions produced in Palu through high-performance liquid chromatography (HPLC) using an immunoaffinity column an a fluorescent detector at an excitation wavelength of 360 nm and an emission wavelength of 440 nm. The standard working chromatogram of aflatoxin gave a peak response at retention times of 28.618 minutes for aflatoxin B1, 21.985 minutes for aflatoxin B2, 17.625 minutes for aflatoxinn G1, and 13.719 minutes for aflatoxin G2. The limit of detection (LOD) values for each standard were : aflatoxin B1 : 0.2607 ng/ml; aflatoxin B2 : 0.0600 ng/ml; aflatoxin G1 : 0.1986 ng/ml; and aflatoxin G2 : 0.0310 ng/ml. The chromatogram results of the 10 fried onion samples analyzed showed no peak response with the same retention time as the standard aflatoxin retention time, so that the 10 samples can be concluded as meet requirements.